Tissue Factor and Atherothrombosis - Saha, D.; S., Saha; Sergeeva, E.G.; Ionova, Z.I.; Gorbach, A.V. (Current Pharmaceutical Design, 2015)
Tissue factor (TF) is known to be the key element in the initiation of the extrinsic pathway of the coagulation cascade and appears to be a critical determinant of atherosclerotic plaque thrombogenicity. TF is needed to produce thrombin from prothrombin. In the extrinsic pathway, TF activates factor Vll. TF is expressed mainly on subendothelial tissues, but TF expression may be induced on endothelial cells by inflammatory mediators such as tumor necrosis factor-alpha (TNF-alpha). Subendothelial TF is responsible for initiating fibrin formation at sites of vascular injury, bloodborne TF may be an important contributor to propagation of the developing thrombus. It has been postulated that the blood-borne TF initiates the thrombogenic stimulus, leading to the formation of larger and more stable thrombus. TF may attach to cellular receptors, which in turn affect the production and release of inflammatory mediators. Baseline plasma TF activity has been demonstrated as an independent predictor for cardiovascular death in patients with acute myocardial infarction. TF is expressed by macrophage-derived foam cells in atherosclerotic plaques. TF levels were higher in atheroma from patients with unstable angina than with stable angina. These results suggest that high levels of TF exposed upon plaque rupture trigger atherothrombosis. Inhibition of TF would be expected to reduce thrombosis associated with a variety of diseases. TF pathway is a potential target for new therapeutic agents that can decrease TF activity, such as active site-inactivated factor VIIa, recombinant TF inhibitor and antibodies against TF or peptides interfering with TF-FVIIa complex activity. Significant clinical forms of atherosclerosis, such as sudden death, myocardial infarction, and stroke have common pathogenesis. The occlusion of the vessel lumen is the result from atherosclerotic plaque rupture/erosion that initiate thrombus formation. This thrombus has complex structure and contains predominantly fibrin in addition to platelets, suggesting an important role for the coagulation cascade in plaque thrombus formation. Tissue factor (TF) is known to be the key element in the initiation of the extrinsic pathway of the coagulation cascade and appears to be a critical determinant of atherosclerotic plaque thrombogenicity.
Keywords: Tissue factor